2010
DOI: 10.1097/gme.0b013e3181bfac3b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on hot flashes in perimenopausal and postmenopausal women-a multicenter randomized clinical trial

Abstract: Our results suggest that acupuncture in addition to usual care is associated with marked clinical improvement in hot flashes and menopause-related symptoms in perimenopausal or postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 57 publications
2
50
0
2
Order By: Relevance
“…The full texts of the remaining 114 articles were assessed, of which 17 were included. These were eight SRs [10][11][12][13][14][15][16][17] and nine RCTs [18][19][20][21][22][23][24][25][26][27] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full texts of the remaining 114 articles were assessed, of which 17 were included. These were eight SRs [10][11][12][13][14][15][16][17] and nine RCTs [18][19][20][21][22][23][24][25][26][27] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…17 In addition, five more RCTs [22][23][24][25][26][27] were included; these were published after the literature search for these SRs. The outcomes measured in most studies were vasomotor symptoms.…”
Section: Climacteric Symptomsmentioning
confidence: 99%
“…The calcitonin gene-related protein (CGRP) is a vasodilator and may mediate these vasomotor symptoms. 17 Based on this hypothesis, previous studies measured the urinary excretion of CGRP after acupuncture, showing a signifi cant decrease of urine CGRP in one study 36 but not in two other studies. 16 37 The true mechanisms of the effect of acupuncture for hot fl ushes needs to be elucidated by further research.…”
Section: Discussionmentioning
confidence: 99%
“…Overall effectiveness of acupuncture compared to usual care was addressed in another study which showed benefi cial effects of acupuncture for 2-month study periods. 17 The limitations of this study include the relatively short period of observation (less than 6 months) and baseline imbalances of patient characteristics and MRS scores, although we employed an analysis of covariance method to adjust observed baseline imbalances of MRS scores, which was not planned in protocol. Standardised acupuncture points and restricted consultation/interaction between the practitioner and participants might diminish the external validity of the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6 In multiple studies, acupuncture has reduced vasomotor symptoms, irrespective of needle placement, depth or type of stimulation. [7][8][9][10][11][12][13] This non-specifi city of the acupuncture intervention has led critics to state that acupuncture effectiveness does not have a specifi c physiological basis beyond that of a placebo, expectation or non-specifi c response. 14 15 This argument needs to be taken seriously, as the placebo effect is varied and potent, 16 and could conceivably be the mechanism by which acupuncture ameliorates menopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%